Experimental determination of latent hardening coefficients in FeMnNiCoCr. (June 2018) - Wu, Y.; Bönisch, M.; Alkan, S.; Abuzaid, W.; Sehitoglu, H.
Abstract: The equi-atomic FeMnNiCoCr high entropy alloy is attracting unprecedented attention due to its exceptional strain hardening behavior extending to large strains and to low temperatures (77K). In this paper, we analyze the nano- to macroscale deformation response of FeMnNiCoCr single crystals and explain variations in strain hardening based on the activation of different twin and slip systems and their interactions. We experimentally determine the latent and the self hardening moduli upon twin-twin, slip-twin, twin-slip and slip-slip interactions. Choosing single crystal orientations that isolate these interactions enables the evaluation of the pertaining hardening moduli without ambiguity. Differing from the earlier experimental approaches employed, which necessitate sample reorientation to quantify the self and latent hardening coefficients, in this work, we demonstrate a novel framework where plastic straining is implemented in a monotonic fashion entailing the latent and primary systems to operate simultaneously. To extract the hardening moduli and to characterize the twin-twin, slip-twin, twin-slip and slip-slip interactions on experimental grounds, <111>tension and <001>compression single crystalline samples are studied by high resolution digital image correlation, electron backscatter diffraction and transmission electron microscopy techniques. The results demonstrate that the magnitude of residual Burgers vectors play a key role in explaining the experimental hardening trends. Highlights: The latent hardening response of FeMnNiCoCr HEAs is investigated when both primary and latent systems are present. The self and latent hardening coefficients are extracted from the experimental stress-strain curves.. The residual Burgers vectors magnitude are used to rationalize the experimental hardening trends.